Characterization of a Novel TtLEA2 Gene From Tritipyrum and Its Transformation in Wheat to Enhance Salt Tolerance - Yang, Zhifen; Mu, Yuanhang; Wang, Yiqin; He, Fang; Shi, Luxi; Fang, Zhongming; Zhang, Jun; Zhang, Qingqin; Geng, Guangdong; Zhang, Suqin (Frontiers in Plant Science, 2022)
Late embryogenesis-abundant (LEA) proteins are critical in helping plants cope with salt stress. “Y1805” is a salt-tolerant Tritipyrum. We identified a “Y1805”-specific LEA gene that was expressed highly and sensitively under salt stress using transcriptome analysis. The novel group 2 LEA gene (TtLEA2-1) was cloned from “Y1805.” TtLEA2-1 contained a 453 bp open reading frame encoding an 151-amino-acid protein that showed maximum sequence identity (77.00%) with Thinopyrum elongatum by phylogenetic analysis. It was mainly found to be expressed highly in the roots by qRT-PCR analysis and was located in the whole cell. Forty-eight candidate proteins believed to interact with TtLEA2-1 were confirmed by yeast two-hybrid analysis. These interacting proteins were mainly enriched in “environmental information processing,” “glycan biosynthesis and metabolism,” and “carbohydrate metabolism.” Protein-protein interaction analysis indicated that the translation-related 40S ribosomal protein SA was the central node. An efficient wheat transformation system has been established. A coleoptile length of 2 cm, an Agrobacteria cell density of 0.55–0.60 OD600, and 15 KPa vacuum pressure were ideal for common wheat transformation, with an efficiency of up to 43.15%. Overexpression of TaLEA2-1 in wheat “1718” led to greater height, stronger roots, and higher catalase activity than in wild type seedlings. TaLEA2-1 conferred enhanced salt tolerance in transgenic wheat and may be a valuable gene for genetic modification in crops.